Greater trochanteric pain syndrome: defining the clinical syndrome. Issue 10 (14th September 2012) - Fearon, Angela M; Scarvell, Jennie M; Neeman, Terry; Cook, Jill L; Cormick, Wes; Smith, Paul N
Abstract : Background: Effective treatment of hip pain improves population health and quality of life. Accurate differential diagnosis is fundamental to effective treatment. The diagnostic criteria for one common hip problem, greater trochanteric pain syndrome (GTPS) have not been well defined. Purpose: To define the clinical presentation of GTPS. Methods: Forty-one people with GTPS, 20 with hip osteoarthritis (OA), and 23 age-matched and sex-matched asymptomatic participants (ASC) were recruited. Inclusion and exclusion criteria ensured mutually exclusive groups. Assessment: the Harris hip score (HHS), a battery of clinical tests, and single leg stance (SLS). Participants identified the site of reproduced pain. Analysis: Fisher's exact test, analysis of variance (ANOVA) informed recursive partitioning to develop two classification trees. Results: Maximum walking distance and the ability to manipulate shoes and socks were the only HHS domains to differentiate GTPS from OA (ANOVA: p=0.010 and <0.001); OR (95% CI) of 3.47 (1.09 to 10.93) and 0.06 (0.00 to 0.26), respectively. The lateral hip pain (LHP) classification tree: (dichotomous LHP associated with a flexion abduction external rotation (FABER) test) had a mean (SE) sensitivity and specificity of 0.81 (0.019) and 0.82 (0.044), respectively. A non-specific hip pain classification tree had a mean (SE) sensitivity and specificity of 0.78 (0.058) and 0.28 (0.080). Conclusions: Patients with LHP in the absence of difficulty with manipulating shoes and socks, together with pain on palpation of the greater trochanter and LHP with a FABER test are likely to have GTPS.